Analisis Strategi Marketing Mix (4P) dalam Peningkatan Tabungan Smart iB Makbul PT Bank Sumut KCP Syari’ah Stabat - Rahmadi Rambe; Muhammad Irwan Padli Nasution; Andri Soemitra; Nurul Hasanah Syah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The Islamic banking industry in Indonesia has experienced steady growth, requiring banks to continuously enhance their products, services, and promotional strategies to attract and retain customers. One of the promising products is the Smart iB Makbul Savings Account offered by PT Bank Sumut Sharia Sub-Branch Office (KCP) Stabat, which is designed to help customers prepare for the Hajj pilgrimage. This study aims to analyze the implementation of the Marketing Mix (4Ps: Product, Price, Place, and Promotion) strategy in increasing the number of customers and the volume of Smart iB Makbul Savings Accounts. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The findings show that the 4Ps strategy has been implemented effectively. The product offers convenient Hajj savings planning, affordable initial deposits, a strategic and accessible location, and integrated promotional activities through personal selling, social media, and collaboration with local Muslim communities. These strategies have successfully increased customer interest and participation in Smart iB Makbul Savings Accounts in Stabat.